Human fascioliasis infection sources, their diversity, incidence factors, analytical methods and prevention measures. Issue 13 (11th July 2018) - Mas-Coma, S.; Bargues, M. D.; Valero, M. A.
Abstract: Human fascioliasis infection sources are analysed for the first time in front of the new worldwide scenario of this disease. These infection sources include foods, water and combinations of both. Ingestion of freshwater wild plants is the main source, with watercress and secondarily other vegetables involved. The problem of vegetables sold in uncontrolled urban markets is discussed. Distinction between infection sources by freshwater cultivated plants, terrestrial wild plants, and terrestrial cultivated plants is made. The risks by traditional local dishes made from sylvatic plants and raw liver ingestion are considered. Drinking of contaminated water, beverages and juices, ingestion of dishes and soups and washing of vegetables, fruits, tubercles and kitchen utensils with contaminated water are increasingly involved. Three methods to assess infection sources are noted: detection of metacercariae attached to plants or floating in freshwater, anamnesis in individual patients, and questionnaire surveys in endemic areas. The infectivity of metacercariae is reviewed both under field conditions and experimentally under the effects of physicochemical agents. Individual and general preventive measures appear to be more complicated than those considered in the past. The high diversity of infection sources and their heterogeneity in different countries underlie the large epidemiological heterogeneity of human fascioliasis throughout.